Identification of familial hypercholesterolemia in acute coronary syndrome patients: are we missing the mark?. (26th April 2021) - Garcia Bras, P; Portugal, G; Castelo, A; Ferreira, V; Reis, J; Mano, T; Grazina, A; Viegas, J; Cardoso, I; Timoteo, A; Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients (P) with familial hypercholesterolemia (FH) have considerable elevation in levels of low-density lipoprotein (LDL) cholesterol and a higher risk of premature coronary artery disease (CAD) and acute coronary syndromes (ACS). However, even in a hospital setting with a high volume of ACS P, the diagnosis of FH frequently goes undetected. The aim of this study was to evaluate the application of the Dutch Lipid Clinic Network (DLCN) Criteria in P admitted for ACS and analyse ACS recurrence, hospitalization and mortality in a 30-day follow-up. Methods: Retrospective evaluation of P with ACS admitted to a tertiary center from 2005 to 2019. Data from the digital files including family history and laboratory tests was analysed and P were followed up for 30 days for hospitalization, recurrent ACS, all cause mortality and cardiovascular (CV) death. Evaluation of tendinous xanthomata, arcus cornealis and genetic analysis was not undertaken. Results: 3811 P were evaluated, mean age 63 ± 13 years, 28% female gender, 1497 P (39%) with active or previous smoking habits, 847 P (22%) with diabetes mellitus, 419 P (11%) with family history of coronary disease, 1340 P (35%) with premature CAD, 53 P (1.4%) with premature cerebral or peripheral vascular disease and 522 (14%) with previous ACS. The mean LDL cholesterol level was 125 ± 43 mg/dL, the mean high-density lipoprotein (HDL) cholesterol level was 40 ± 16 mg/dL and the mean triglyceride level was 132 ± 89 mg/dL. The diagnosis at hospital admission was unstable angina (UA) in 189 P (5%), non-ST-segment elevation myocardial infarction (NSTEMI) in 1024 P (27%) and ST-segment elevation MI (STEMI) in 2598 P (68%). The hospital mortality rate was 4.3% (163P). Applying the DLCN criteria, 3089 P (81%) had a score of <3 ("unlikely FH"), 675 P (17.7%) a score of 3 to 5 ("possible FH"), 41 P (1.1%) a score of 6 to 8 ("probable FH") and 1 P (0.03%) a score of >8 ("definite FH"). Stratifying according to ACS type: among UA, 31 P (16%) had "possible FH" and 4 P (2.1%) had "probable FH". Among NSTEMI, 145 P (14.2%) had "possible FH", 9 P (0.9%) "probable FH" and 1 P (0.03%) had "definite FH". Finally, among STEMI P, 497 P (19.1%) had "possible FH" and 28 P (1.1%) had "probable FH". In a 30-day follow-up, there was an all cause mortality of 2% (78 P) and a CV death of 1.3% (49P), while the all cause hospitalization rate was 3.5% (134P) and the admission rate for recurrent ACS was 1.7% (65P). The DLCN criteria score was significantly correlated with CV death (OR 1.25, CI 95% 1.04-1.50, p = 0.020) and admission for recurrent ACS (OR 1.19, CI 95% 1.04-1.36, p = 0.04). Conclusion: Application of the DLCN criteria in P admitted for ACS revealed 675 P (17.7%) with "possible FH" and 41 P (1.1%) with "probable FH" as well as show significant correlation with CV death and recurrent ACS. Routine assessment of these criteria can be an accessible tool to stratify likelihood of FH and proceed accordingly to genetic testing.